For the polynomial below, the -2 is a zero.
f(x)= x^3 - 2x^2 - 6x + 4
Express f(x) as a product of linear factors.
Use fractions or radicals in answers not decimals.
Check the root -2: f(-2)=-8-8+12+4=0.
Then divide f(x) by (x+2):
x^3-2x^2-6x+4 = x^2(x+2)-2x^2-2x^2-6x+4 = x^2(x+2)-4x^2-6x+4 = x^2(x+2)-4x(x+2)+8x-6x+4 =
x^2(x+2)-4x(x+2)+2x+4 = x^2(x+2)-4x(x+2)+2(x+2) = (x+2)(x^2-4x+2).
To divide (x^2-4x+2) find its zeros, this is the quadratic equation:
x1,2 = 2+-sqrt(4-2) = 2+-sqrt(2). (I used formula for the even second coefficient).
The answer: f(x) = (x+2)(x-2-sqrt(2))(x-2+sqrt(2)).
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?